Vecindad civil de la mujer casada: nuevas reflexiones en torno a la inconstitucionalidad sobrevenida del art. 14.4 C.c. y la retroactividad de la Constitución española en relación a los modos de adquisición de su vecindad civil - Abarca Junco, Ana-Paloma; Vargas-Gómez Urrutia, Marina (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
The rulings of the Supreme Court of Navarra (Tribunal Superior de Justicia de Navarra) dated March 3, 1994, the Provincial Court of Barcelona (Audiencia Provincial de Barcelona) dated November 4, 2003 and the Supreme Court (Tribunal Supremo) dated September 14, 2009 allow for a new analysis on the determination of the civil residence of a married woman, acquired before the Spanish Constitution, in relation to the law applicable to the succession. The Tribunal Superior de Justicia de Navarra confirms civil residence of the husband -acquired in 1965 - while adjusting the result of the matter through the application of another law (catalana) given the particular circumstances of the case. The Audiencia Provincial de Barcelona denies the application of Navarran laws to the wife’s inheritance and considers Catalan laws to be applicable on the basis that the relationship of a married woman to her husband’s civil residence ceased to have effects upon effectiveness of the current Spanish Constitution, retroactively applying the same to deny the effectiveness of Article 14.4 of the Civil Code (in its version in force at that time.) The Supreme Court upholds such a ruling on the grounds of a sudden unconstitutionality of that article of the Civil Code, which it argues based on the ruling dated February 14, 2002. This paper aims to highlight some problems and develop a proposed solution which is not necessarily consistent with the legal grounds of the judgments discussed